JARIMAH BAGI PELAKU TINDAK PIDANA LINGKUNGAN HIDUP PERSPEKTIF HUKUM ISLAM (IAIN Tulungagung, 2023)
Lately in Indonesia there have been frequent natural disasters such as landslides. One of the causes of natural disasters is due to human actions that use nature carelessly, where humans in managing nature do not pay attention to ecosystems in a comprehensive and well-planned manner. Allah SWT has provided provisions that humans are encouraged to always take care of their environment as well as possible so that it remains sustainable. Human behavior that does not have a sense of responsibility and always causes damage to nature must certainly be punished accordingly (jarimah) for their actions. This paper aims to describe the exact form of jarimah imposed on the perpetrators of environmental destruction. Environmental destruction can be categorized as a criminal act. The purpose of imposing a finger on the perpetrators of environmental destruction is so that the perpetrators are wary of what they have done. The forms of jarimah are very diverse, therefore it is necessary to have an appropriate analysis in giving jarimah to perpetrators of environmental crimes.